Production performance of Alabio ducks (Anas platyrhynchos Borneo) under different levels of drinking water salinity - Sulaiman, Abrani; Rahmatullah, Surya; Effendi, Hefni; Simanungkalit, Gamaliel (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: To examine the effects of the salinity level of drinking water on the egg production and quality of Alabio ducks. Materials and Methods: A total of 60 female Alabio ducks, aged 6 months, were subjected to this study. All ducks were kept in stage-type cages (1 m length × 1 m width × 0.5 m height), where each cage was inhabited by 4 ducks for 56 days of experimentation. All ducks were offered a mixed ration ad libitum for laying ducks, according to the nutritional requirements for egg-type ducks. The treatment in this study was drinking water with five stratified salinity levels, namely P0 = freshwater (0% salinity); P1 = water with a salinity of 0.75 practical salinity unit (PSU) (equal to 0.75 g NaCl/l); P2 = water with a salinity of 1.5 PSU (1.5 gm/l); P3 = water with a salinity of 2.5 PSU (2.5 gm/l); and P4 = water with a salinity of 3 PSU (3.0 gm/l). Observations were made on water intake, feed intake, egg production, and egg quality (egg weight, egg shape index density, shell proportion, shell thickness, yolk index, albumen index, and Haugh unit). Results: The results showed that the difference in salinity levels in drinking water from 0.75 PSU to 3 PSU did not affect water intake, feed intake, egg production, or egg quality of Alabio ducks for the first 56 days of the laying period (p > 0.05). Conclusions: It was concluded that Alabio ducks have a good tolerance for drinking water salinity of up to 3 PSU, or equal to 3 gm/l NaCl. J. Adv. Vet. Anim. Res., 9(2): 241–245, June 2022 http://doi.org/10.5455/javar.2022.i589